Role of olfaction and vision cues in feeding behavior and alarm reaction in the catfish pintado, Pseudoplatystoma corruscans - Giaquinto, Percilia Cardoso [UNESP]; Hoffmann, Anette (Springer Tokyo, 2010)
Experiments were performed to investigate senses that are essential for mediating fright reaction and food behavior in Pseudoplatystoma corruscans, pintado. The dilemma "to feed or to flee" was also analyzed in fishes with intact and sectioned olfactory tracts, stimulated by alarm substance extracts and food. Fishes were arranged into five groups: fish with intact lateral olfactory tracts (LOT), fish with intact medial olfactory tract (MOT), fish with tracts totally sectioned (TOTAL, both LOT and MOT), sham operated, and nonoperated fish. The five groups were submitted to either alarm substance extract and food stimulus or to distilled water (control) and food stimulus. Fish reacted to food independently of which tract (LOT, MOT or TOTAL) was sectioned; vision seems necessary and elemental to detect and deflagrate food response. Latency of the responses to each reaction was different between groups. None of the fish with sectioned tracts reacted to alarm substance extract, while sham- and nonoperated fish showed the typical alarm behavior response, leading to the conclusion that olfaction is essential for mediating alarm response. These results indicate that others sense systems (e.g., vision) are sufficient to trigger and elicit feeding behavior and that olfaction is not necessary to fully maintain food detection to qualitative and quantitative extent. However, olfactory tract integrity seems to be required for mediation of alarm reaction in P. corruscans.
Keywords: Fish; Olfaction; Olfactory tract; Feeding behavior; Alarm reaction; Alarm substance